Evaluasi Kinerja Unit Traveling Band Screen dengan Menghitung Ulang Daya Motor Penggerak dan Dampak Tegangan Kerjanya Pada Bucket Chain - Widyanto, Susilo; Kurdi, Ojo (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
Traveling band screen (TBS) of the intake system has an important function in the power plant system operation which directly relates to the condenser efficiency. TBS utilizes to screen seawater debris before pumped into the condenser unit. The driver motor power of TBS must be able to drive the mechanical system in a condition where the screen is covered by debris at a certain level. This paper presents the evaluation of the driver motor power of TBS which operated in 2x660 MW power plant, where the existing motor (2 hp) often shuts down at the undetermined blockage level of the TBS screen. The calculation results show that the use of 2 HP motor power can only drive the mechanical system at blockage level of 13%. With replacement of the 5 HP motor, the operation limit of the TBS unit can be increased to the blockage level of 36%.Â The maximum stress of the bucket chain structure is around of 127 MPa.